2022
DOI: 10.1038/s41420-021-00785-6
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from adipose-derived mesenchymal stem cells alleviate sepsis-induced lung injury in mice by inhibiting the secretion of IL-27 in macrophages

Abstract: Acute lung injury (ALI) represents a frequent sepsis-induced inflammatory disorder. Mesenchymal stromal cells (MSCs) elicit anti-inflammatory effects in sepsis. This study investigated the mechanism of exosomes from adipose-derived MSCs (ADMSCs) in sepsis-induced ALI. The IL-27r−/− (WSX-1 knockout) or wild-type mouse model of sepsis was established by cecal ligation and puncture (CLP). The model mice and lipopolysaccharide (LPS)-induced macrophages were treated with ADMSC-exosomes. The content of Dil-labeled e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…MSCs-derived exosomes have shown good therapeutic effects in preclinical models of ALI/ARDS. MSCs-derived exosomes have been shown to inhibit macrophage aggregation in lung tissue, suppress IL-27 secretion, reduce the levels of pro-inflammatory factors in lung tissue, and improve the survival rate of mice ( 79 ). Wei et al.…”
Section: The Safety and Efficacy Of Exosomes In Animal Experiments An...mentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs-derived exosomes have shown good therapeutic effects in preclinical models of ALI/ARDS. MSCs-derived exosomes have been shown to inhibit macrophage aggregation in lung tissue, suppress IL-27 secretion, reduce the levels of pro-inflammatory factors in lung tissue, and improve the survival rate of mice ( 79 ). Wei et al.…”
Section: The Safety and Efficacy Of Exosomes In Animal Experiments An...mentioning
confidence: 99%
“…In addition, exosomes can also bind to specific receptors on the surface of target cells. Wang et al found that MSCs-derived exosomes could inhibit the aggregation of pulmonary macrophages and suppressed the synthesis and release of IL-27, and decrease the contents of IL-6, TNF-a, and IL-1b, thus alleviating sepsis-induced lung injury (79). Injection of recombinant IL-27 reversed the protective effect of exosomes on sepsis-induced lung injury.…”
Section: Anti-inflammatory Effects Of Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-27 is a cytokine that increases during sepsis, and its suppression could be a potential target in treating sepsis [ 92 ]. ASC-Exos have been shown to attenuate lung injury in septic mice by decreasing pulmonary macrophages and reducing their IL-27 expression [ 93 ]. The molecular mechanism of action of SC-Exos could be related to their miRNA content.…”
Section: Stem Cell-derived Exosome Therapeutic Effect On Lung Diseasesmentioning
confidence: 99%
“…A study identified exosomal miR-16-5p derived from ASC as a regulator of TLR4 in septic mice. By this mechanism, ASC-Exos promoted macrophage polarization and alleviated sepsis-induced lung injury [ 93 ].…”
Section: Stem Cell-derived Exosome Therapeutic Effect On Lung Diseasesmentioning
confidence: 99%